„Pieśń duchowa” św. Jana od Krzyża – przekład,aluzje biblijne i symbolika - Krzysztof Bardski (Warszawskie Studia Teologiczne)
The article presents a new translation into Polish of the sixteenth-century poem The Spiritual Canticle of Saint John of the Cross. The translation was made in the form of an eight-syllable verse, without rimes. In the introduction, we presented earlier Polish translations of the work, and in footnotes, we emphasized the issues related to symbolism and biblical allusions.